CAR T-cell therapy and the onco-nephrologist - Salvino, Marco Aurelio; Mussetti, Alberto; Peña, Marta; Paviglianiti, Annalisa; Carreira, Abel Santos; Rizky, Daniel; Sureda, Anna (Frontiers in Nephrology, 2024)
Cell therapy, specifically the revolutionary chimeric antigen receptor (CAR) T-cell therapy, has transformed the landscape of oncology, making substantial strides in practical treatment approaches. Today, established guidelines for diseases such as lymphomas, myelomas, and leukemias actively advocate the utilization of these once-unconventional therapies. The practical impact of these therapies is underscored by their unparalleled efficacy, reshaping the way we approach and implement treatments in the realm of oncology. However, CAR T-cell therapy, with its performance in anti-tumor aggression through cellular action and inflammatory response, also comes with various adverse events, one of which is kidney injury. Therefore, the management of these side effects is extremely important. The integration of knowledge between oncologists and specialized nephrologists has led to the emergence of a new sub-area of expertise for onco-nephrologists specializing in managing kidney complications from immune effector therapies.